Deotorisasi Hadis di dunia maya: Analisis penggunaan hadis-hadis di youtube dalam akun The Sungkars Family - muhammad adli (CV. Ulil Albab Corp, 2023)
This study examines the deauthorization of hadith in cyberspace. The focus of the study in this research is to find out the extent to which hadith contestation is involved. This research uses qualitative methods that originate from observations on the context of reality and digital data analysis. In other words, this research has a content analysis model, which according to Barcus in Suriani is a scientific analysis model related to the issue of an information content. The approach used in this research is descriptive-exportative to provide a comprehensive and complete understanding of the contestation of hadith in the mass media. The results of this study conclude that the impact of the contestation of hadith on social media also makes the authorization of the hadith a more special concern. In addition, there are several foundations of hadith that are used as principles in such activities. In addition, there is a need to pay more attention to the authorization in the transmission of the Prophet's hadith, to ensure the reader about the validity of an issue and also the credibility of the hadith by being more thorough.